PENGARUH PROMOSI MEDIA SOSIAL DAN ULASAN ONLINE TERHADAP KEPUTUSAN BELI VIA BRAND AWARENESS - Dani Setiawan; Alimuddin Rizal Rivai (STKIP Persada Khatulistiwa Sintang, 2025)
Micro, Small, and Medium Enterprises (MSMEs) require effective marketing strategies to expand their market share, one of which is through the utilization of social media. This study was motivated by the phenomenon of increasing social media promotions and online customer reviews on the Durian Traveler Store’s accounts, which are presumed to influence brand awareness and purchase decisions. The purpose of this study is to analyze the effect of social media promotion and online customer reviews on purchase decisions, with brand awareness as an intervening variable. The research method used is quantitative with a survey approach. Primary data were collected through questionnaires distributed to 100 respondents using purposive sampling techniques, with criteria of consumers who have purchased the product more than once. Data analysis includes validity, reliability, classical assumption, multiple linear regression, and Sobel tests. The results show that social media promotion and online customer reviews have a positive and significant effect on brand awareness, while brand awareness significantly affects purchase decisions. Brand awareness is also proven to mediate the relationship between social media promotion and online customer reviews on purchase decisions. This study is limited to a single MSME object; therefore, future research is suggested to expand the sample to other business sectors to strengthen the generalization of the findings.